Dimensions of difficulty in children reported to have an autism spectrum diagnosis and features of extreme/'pathological' demand avoidance. Issue 3 (12th October 2017) - O'Nions, Elizabeth; Viding, Essi; Floyd, Caroline; Quinlan, Emma; Pidgeon, Connie; Gould, Judith; Happé, Francesca
Abstract : Background: A subset of individuals with autism spectrum disorder (ASD) resemble descriptions of extreme/'pathological' demand avoidance, displaying obsessive avoidance of everyday demands and requests, strategic or 'socially manipulative' behaviour and sudden changes in mood. Investigating challenging presentations using dimensional description may prove preferable to identifying subgroups. However, there remains an imperative to explore which behavioural traits appear most problematic to inform quantitative investigation. This study provides an in‐depth exploration of parent perspectives on maladaptive behaviour in children reported to have an autism spectrum diagnosis and features of extreme/'pathological' demand avoidance. Method: Parents completed a tailored semistructured interview about their child's behaviour, focusing on difficulties relevant to descriptions of extreme/'pathological' demand avoidance. The 26 interviews rated as scoring above threshold for 'substantial' features of extreme/'pathological' demand avoidance on relevant indicators were analysed qualitatively using a general inductive approach. Results: New themes that emerged from these data included attempts by the child to control situations and others' activities. Avoidance behaviours in this sample could be described as 'strategic' rather than 'manipulative'. A range of factors, including a negative emotional response to demands, but also phobias, novelty, and uncertainty, were perceived to play a role in triggering extreme behaviour. Conclusions: These descriptions highlight the importance of systematically measuring noncompliance, attempts to control situations and others' activities, and extreme mood variability in individuals with ASD. These dimensions represent important targets for intervention, given their considerable impact on daily life. Abstract : Read the full Commentary on this article at doi:10.1111/camh.12273 Read the full Response to the Commentary on this article at doi:10.1111/camh.12287